Effect of Discharge Variations on Flow Characteristics in Chute - Syabrina Arvadelia; Firyaal Nabila; Bayu Krisna Wisnulingga; Ngakan Putu Purnaditya; Bambang Adhi Priyambodho; Subekti Subekti (JURUSAN TEKNIK SIPIL, 2026)
The utilization of water resources in open channel systems is critical to support drainage efficiency and surface flow control, especially in areas with steep topographic conditions. Chute are used to overcome flows with large base slopes so that channels can be designed with sub-critical bottom slopes and do not cause erosion. This study aims to analyze the effect of discharge variations on the characteristics of flow and hydraulic jump on chute. The research method uses a physical model using flume conducted at the Integrated Laboratory of Sultan Ageng Tirtayasa University. Based on the results of the study, it was shown that the increase in flow discharge at the constant slope (1:1) and the difference in the constant height of the chute (0.2 m) resulted in an increase in water level elevation and an increase in velocity upstream, retreat and downstream. The type of flow that occurs upstream is an almost critical flow (Fr = 1), while the type of flow in the upstream and downstream is a supercritical flow (Fr > 1). The hydraulic jump length and hydraulic jump height have increased due to the increase in flow discharge. The flow velocity and froude numbers from upstream to upstream have increased, while the flow velocity and froude numbers from downstream have decreased.